Gender Differences of Studentsâ€™ Writing Ability in Descriptive Text - Wiyanto, Muhammad Saibani; Asmorobangun, Panji Wisnu (JOLLT Journal of Languages and Language Teaching, 2020)
Language has an important role for every member of the speech community. The connection between language and society is recognized as the main interest of sociolinguistics. Nowadays, sociolinguistic has involved many significant research topics. One of them is the relationship between gender and language. Studies about gender differences have been conducted for many years, which also deals with the use of a language as a foreign language. For instance, studying English as a foreign language (EFL) among the nonnative speakers and its gender-sensitive investigation. The current article provides insights on gender differences among senior high school students with a focus on their writing ability. The purposes of this article were to find the linguistic feature that male and female students tend to use and to find out the gender differences reflected on the students writing ability. The article used a qualitative design with document analysis as the approach. The subject of this article was one class of X MIPA 2 at MAN 6 Jombang. The source of the data was studentsâ€™ writings, while the data were all linguistics components of the studentsâ€™ works. The data contain some types of linguistic features based on Mulacâ€™s theory. This article found four linguistic features used by the students. It can be concluded that males often used locative feature and females often used a reference to quantity feature and â€œIâ€ reference feature.Â